THE ENERGETIC POTENTIAL OF SPEECH PAUSES - Kalyta, Alla (Advanced Education, 2018)
In the paper on the basis of a systemic methodological approach within the framework of speech energetic theory the author advances a theoretical insight into the nature of psycho-energetic generation and decoding of speech pauses in communication as well as offers a theoretical and conceptual solution to the problem of defining the dimensionless criterion able to quantitatively evaluate the levels of emotional and pragmatic potentials of certain speech segments at their pausal juncture, or boundary, termed in the paper as “a pausal jump”. The paper elaborates the formula defining the criterion of specific pausal jump of emotional and pragmatic potentials of the adjacent speech segments, being derived on the basis of the substantiated conceptual assumptions and methodological conditions. The author comes to the conclusion that the offered quantitative criterion will (1) advance the possibility to classify the energetic properties of emotional utterances, and (2) will allow the researcher to make up the speakers’ typical psycho-energetic portraits.